Pengaruh Kompensasi, Lingkungan Kerja, dan Kepuasan Kerja, terhadap Motivasi Kerja Pegawai Kecamatan Sekupang Kota Batam - Christian Mongan, Yohanes; Langgeng Ratnasari, Sri; Puji Lestari, Etty (Bahtera Inovasi, 2023)
This study aims to determine the effect of compensation, work environment, job satisfaction on the work motivation of employees in Sekupang District, Batam City, either partially or simultaneously. This research is descriptive with causal effect design. The sample in the study of all 110 employees was taken by census method. In the research conducted by respondents who returned 55 questionnaires. Data analysis used multiple linear regression. The results showed that there were effects of compensation, work environment, and job satisfaction on employee motivation both partially and simultaneously, meaning that the better the respondents' perceptions about the compensation they received, the job satisfaction they felt in carrying out their work, and the work environment they felt, the better their motivation will be.